The differential production cross section of the [Formula: see text] (1020) meson in [Formula: see text] = 7 TeV [Formula: see text] collisions measured with the ATLAS detector - Aad, G. (Eur Phys J C Part Fields, 2014)
A measurement is presented of the [Formula: see text] production cross section at [Formula: see text] = 7 TeV using [Formula: see text] collision data corresponding to an integrated luminosity of 383 [Formula: see text] , collected with the ATLAS experiment at the LHC. Selection of [Formula: see text] (1020) mesons is based on the identification of charged kaons by their energy loss in the pixel detector. The differential cross section is measured as a function of the transverse momentum, [Formula: see text] , and rapidity, [Formula: see text] , of the [Formula: see text] (1020) meson in the fiducial region 500 [Formula: see text] 1200 MeV, [Formula: see text] 0.8, kaon [Formula: see text] 230 MeV and kaon momentum [Formula: see text] 800 MeV. The integrated [Formula: see text] -meson production cross section in this fiducial range is measured to be [Formula: see text] = 570 [Formula: see text] 8 (stat) [Formula: see text] 66 (syst) [Formula: see text] 20 (lumi) [Formula: see text] .